2006
DOI: 10.1111/j.1742-4658.2006.05557.x
|View full text |Cite
|
Sign up to set email alerts
|

A designed curved DNA segment that is a remarkable activator of eukaryotic transcription

Abstract: To identify artificial DNA segments that can stably express transgenes in the genome of host cells, we built a series of curved DNA segments that mimic a left‐handed superhelical structure. Curved DNA segments of 288 bp (T32) and 180 bp (T20) were able to activate transcription from the herpes simplex virus thymidine kinase (tk) promoter by approximately 150‐fold and 70‐fold, respectively, compared to a control in a transient transfection assay in COS‐7 cells. The T20 segment was also able to activate transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Therefore, histones could be a key factor for the intranuclear disposition of the exogenous DNA. In agreement with this hypothesis, transgene expression is affected by the introduction of DNA sequences with high and low histone affinities into plasmid DNAs (Nishikawa et al, 2003;Sumida et al, 2006;Kamiya et al, 2007Kamiya et al, , 2009.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, histones could be a key factor for the intranuclear disposition of the exogenous DNA. In agreement with this hypothesis, transgene expression is affected by the introduction of DNA sequences with high and low histone affinities into plasmid DNAs (Nishikawa et al, 2003;Sumida et al, 2006;Kamiya et al, 2007Kamiya et al, , 2009.…”
Section: Introductionmentioning
confidence: 82%
“…The intranuclear disposition of the delivered plasmid is an important factor in efficient transgene expression (Kamiya et al, 2003). Nucleosomes are formed on non-integrated plasmid DNAs (Reeves et al, 1985), and the introduction of high and low histone-affinity DNA sequences into plasmid DNAs influences transgene expression (Nishikawa et al, 2003;Sumida et al, 2006;Kamiya et al, 2007Kamiya et al, , 2009. Moreover, decreased expression efficiency (silencing) seems to be accompanied by increased histone binding, not by histone modification (Ochiai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of the left-handedly curved sequence on transgene expression from plasmids in mouse liver Previously, Sumida et al 12 constructed various plasmids containing the left-handedly curved sequence in the upstream region of the thymidine kinase (tk) promoter, and compared the luciferase expression in cultured cells when the plasmid DNAs were delivered by electroporation. The insertion of the T20, T24, T28, T32, T36 and T40 sequences (Figure 1) markedly enhanced the luciferase expression.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was shown that a designed, left-handedly curved DNA sequence (TTTTT[CATGTTTTT] 3 , T4 0 ) could activate a promoter in plasmid DNA, in cultured mammalian cells and mouse liver. 9--11 Recently, Sumida et al 12 found that longer versions of the left-handedly curved DNA sequence (connection of the T4 0 sequence in series, named Tn, n ¼ 20--40, Figure 1) markedly enhanced transgene expression in cultured cells. These sequences would be quite interesting tools for controlling the intranuclear disposition, if they were also effective in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the regulation of histone binding to the exogenous DNA would be an important factor for transgene expression, and hence for the intranuclear disposition of the plasmid DNA (Kamiya et al, 2003). Indeed, transgene expression was influenced by the introduction of DNA sequences that modulate histone dynamics into plasmid DNAs (Fukunaga et al, 2012;Kamiya et al, 2007Kamiya et al, , 2009Nishikawa et al, 2003;Sumida et al, 2006). Recently, histones have been used as vehicles for plasmid DNAs (Kaouass et al, 2006 and references therein).…”
Section: Introductionmentioning
confidence: 99%